Front Matter Jurnal ASET (Akuntansi Riset) Vol 8 No 2 July-December 2016 - Setiawan, Yana (Jurnal ASET (Akuntansi Riset), 2016)
Front Matter Jurnal ASET (Akuntansi Riset) Vol 8 No 2 July-December 2016